P009 The effects of low-dose morphine on sleep and breathlessness in chronic obstructive pulmonary disease. (9th November 2022) - Altree, T; Loffler, K; Toson, B; Currow, D; Eckert, D
Abstract: Introduction: Low-dose morphine is prescribed for refractory breathlessness in chronic obstructive pulmonary disease (COPD). Preliminary investigations suggest improved perceived sleep quality, although concerns exist regarding opioid-induced sedation. This study assessed the effects of morphine on subjective sleep quality and alertness, and potential links between sleep quality and breathlessness. Methods: Analysis of sleep questionnaire and breathlessness data at baseline and after one week of low-dose slow-release morphine versus placebo according to a double-blind randomised controlled design was performed. Participants were randomised to placebo, 8mg or 16mg/day oral morphine for one week (before further dose escalation). Epworth Sleepiness Scale (ESS), Karolinska Sleep Score (KSS), Leeds Sleep Evaluation Questionnaire (LSEQ) and breathlessness severity scores were assessed. Dose effects on sleep measures were assessed via linear regression (including baseline sleep measures). Drug effects on the relationship between sleep quality and breathlessness were assessed via linear mixed models with random effects and three-way interaction between sleep measures, dose, and visit. Results: 156 patients were randomised as follows: 8mg, n=55; 16mg, n=51; placebo n=50. Overall, there was a neutral effect of morphine on ESS, KSS, and LSEQ (all p>0.05). Morphine did not modify the relationship between sleep measures and breathlessness. Discussion: Despite safety concerns, one week of morphine did not negatively impact subjective sleep or daytime alertness measures. There was no clear relationship between morphine's effects on sleep and next-day breathlessness perception. Objective data assessing sleep and next-day alertness are required to further explore potential links between sleep and breathlessness in people with COPD.